THE APPLICATION OF ENTREPRENEURSHIP STRATEGIC MANAGEMENT TO CLASSROOM MANAGEMENT - Dewi, Liliana (Universitas Brawijaya, Indonesia, 2019)
Handling students in a big class (above fifty students) often triggers many problems. One major problem is regarding active participation of students in the class. In a big class, the participation level of students is often low since the class is usually dominated only by dominant students. As educators, we all want full participation of all students in our class. A study is conducted to solve the problem of student participation in a big class. One thing a teacher can do is to design the class in such a way that the students have an opportunity to develop his or her full participation. Qualitative research in Marketing Management class in University is being done to observe whether a particular classroom management design can activate student participation. This classroom management design is made to enable students experiencing a real work atmosphere where productivity and social skills (which influence student participation in the class) are needed. According to education experts, traditional classroom management is not sufficient to develop productivity and social skills. Therefore a structured management system is applied in managing the research class. In addition, an entrepreneurial profile (desire for responsibility) for each student is collected to decide which student fits to become a group coordinator. The result of the research reveals that students can play the role of coordinators (upper management); they can actively participate in the class and communicate with the lecturer, as well as with the other students who are not coordinators. The students are proven to actively communicate based on the hierarchy which is purposively created by the lecturer.